2016
DOI: 10.1080/13102818.2016.1184588
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization, expression pattern and function analysis of theOsHSP90family in rice

Abstract: The HSP90 is an abundant chaperone protein that is conserved in all eukaryotes. The main function of HSP90 is to assist other proteins to fold properly. In this study, we uncovered and analysed nine OsHSP90 (OsHSP90-1-OsHSP90-9) family members in rice Nipponbare, in which three distinct motifs were identified. All the HSP90 proteins were classified into three major groups (I, II, III) by phylogenetic analysis. The expression of OsHSP90 family in 10 tissues was examined by real-time polymerase chain reaction (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Heat shock proteins (Hsps) and the diverse families of small Hsps in plants are known to be induced or repressed in response to biotic and abiotic stresses . In addition to their roles as molecular chaperones that prevent protein misfolding, some Hsps regulate TFs for a diverse set of genes, and several Hsps are involved in adaptation of Saccharomyces cerevisiae to the auxinic herbicide 2,4‐D .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock proteins (Hsps) and the diverse families of small Hsps in plants are known to be induced or repressed in response to biotic and abiotic stresses . In addition to their roles as molecular chaperones that prevent protein misfolding, some Hsps regulate TFs for a diverse set of genes, and several Hsps are involved in adaptation of Saccharomyces cerevisiae to the auxinic herbicide 2,4‐D .…”
Section: Discussionmentioning
confidence: 99%
“…wileyonlinelibrary.com/journal/ps Heat shock proteins (Hsps) and the diverse families of small Hsps in plants are known to be induced or repressed in response to biotic and abiotic stresses. 94,95 In addition to their roles as molecular chaperones that prevent protein misfolding, some Hsps regulate TFs for a diverse set of genes, 96 and several Hsps are involved in adaptation of Saccharomyces cerevisiae to the auxinic herbicide 2,4-D. 97 In A. fatua, we observed constitutive reduction of three Hsp DEGs (5629.3793, 5629.2548 and 7001.7) and one Hsp protein (spot 797) in MHR4 A. fatua (Tables 3 and 4). The functionally related DEG 4994 (cyclophilin-like peptidylprolyl isomerase), which catalyzes a rate-limiting step in protein folding, 98 was also constitutively reduced in MHR4 plants.…”
Section: Redox Maintenance/stress Responsementioning
confidence: 99%
“…In rice, OsAHL1 was shown to directly induce HSP101 and HSP90 expression leading to drought resistance (Zhou et al, 2016). OsHSP90-2 and OsHSP90-4 were also found up-regulated after drought, cold, heat and salt stresses (Zhang et al, 2016). When introduced in E. coli, OsHSP90-2 was sufficient to induce resistance to heat, high salinity and drought (Zhang et al, 2016).…”
Section: Future Perspectives Of Technology Transfer To Cropsmentioning
confidence: 99%
“…OsHSP90‐2 and OsHSP90‐4 were also found up‐regulated after drought, cold, heat and salt stresses (Zhang et al ., ). When introduced in E. coli , OsHSP90‐2 was sufficient to induce resistance to heat, high salinity and drought (Zhang et al ., ). A similar modulation of HSFs and HSPs was found in tomato in response to heat, drought and salinity (Fragkostefanakis et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…At present, the specific mechanism by which heat tolerance is enhanced in E. coli recombinants transformed with OsDUF872.2 remains unclear. It has been reported that the overexpression of some heat shock protein genes can enhance the heat tolerance in E. coli [39][40][41][42]. Under heat conditions, it is possible that OsDUF872.2 interacts with some heat shock protein, and the proteinprotein interaction can lead to improve the heat stress resistance in transgenic E. coli.…”
Section: Osduf8722 Improved Heat Resistance In Transgenic E Colimentioning
confidence: 99%